Analysis of Spatial Geographic Data on The Event of Dengue Hemorrhagic Fever - Nur, Radian; Husaini, Husaini; Suhartono, Eko; Noor, Meitria Syahadatina; Wydiamala, Erida (Jurnal Berkala Kesehatan, 2024)
Dengue fever (DHF) in Indonesia is increasing and spreading. This is due to weak early warning systems and risk factors for disease spread that are influenced by geospatial changes. This study employs a systematic review approach with meta-analysis to ascertain the impact of regional spatial data on dengue incidence. The results showed that rainfall tended to have a large effect on dengue incidence with an ES value of (0.44), temperature had a very small effect on dengue incidence with an ES value of (0.02), humidity had a moderate effect on dengue incidence with an ES value of (0.18), and wind speed tended to have a very large effect on dengue incidence with an ES value of (1.19). Temperature change had a significant influence on the incidence of DHF. Rainfall, temperature change, humidity and wind speed had an I-squared value (OR variation caused by heterogeneity) of 100% while wind speed was 0%. Rainfall, temperature change and humidity tended to have variable results so that they had a strong influence on the results of the meta-analysis, while wind speed tended to be homogeneous, allowing for high research bias.